All-silicon non-volatile optical memory based on photon avalanche-induced trapping - Yuan Yuan; Yiwei Peng; Stanley Cheung; Wayne V. Sorin; Sean Hooten; Zhihong Huang; Di Liang; Jiuyi Zhang; Marco Fiorentino; Raymond G. Beausoleil (Communications Physics)
Abstract Implementing on-chip non-volatile optical memories has long been an actively pursued goal, promising significant enhancements in the capability and energy efficiency of photonic integrated circuits. Here, we demonstrate an non-volatile optical memory exclusively using the most common semiconductor material, silicon. By manipulating the photon avalanche effect, we introduce a trapping effect at the silicon-silicon oxide interface, which in turn demonstrates a non-volatile reprogrammable optical memory cell with a record-high 4-bit encoding, robust retention and endurance. This silicon avalanche-induced trapping memory provides a distinctively cost-efficient and high-reliability route to realize optical data storage in standard silicon foundry processes. We demonstrate its applications in trimming in optical interconnects and in-memory computing. Our in-memory computing test case reduces energy consumption by approximately 83% compared to conventional optical approaches.